Cardiovascular Stability during Off-Pump Coronary Artery Bypass (OPCAB) Surgery- A Comparison between Combined High Thoracic Epidural Anaesthesia (HTEA) with TIVA and TIVA alone - Azad, SI; Beg, AK; Chowdhury, AYFE; Khatun, UHS (Cardiovascular Journal, 2010)
Background: In Bangladesh, although OPCAB surgery are done, the number of centers are limited and as a result, studies on this subject are also few. Consequently, there are no exclusive data regarding the best anaesthetic technique in the context of superior haemodynamic stability. This study has been undertaken with a view to find out whether a combined HTEA with GA (TIVA) is safe and more efficient in providing overall cardiovascular stability. The common challenges for the cardiac anaesthesiologist during off pump coronary artery surgery (OPCAB) to maintain optimal cardiovascular parameters such as heart rate, blood pressure, CVP and arrhythmias during the different stressful surgical events and multiple cardiac manipulations, providing adequate myocardial protection, are sometimes difficult. This study has been undertaken with a view to find out whether a combined HTEA with TIVA is safe and more efficient in providing overall cardiovascular stability. Method: Sixty patients aged between 40-70 years, without having any coagulopathy disorder , any emergency surgery or left main disease scheduled for CABG on beating heart were enrolled in prospective, randomized observational comparative study. Patients were divided in two groups. In group A patients received TIVA alone and in group B patients received high thoracic epidural anaesthesia with TIVA. The parameters including heart rate , SPO2 , CVP , arterial blood pressure , rate pressure product , arrhythmia in ECG, were recorded before induction, during induction , intubation and during different events of the surgery ( skin incision, sternotomy, pericardiotomy, coronary artery anastomosis with graft , sternum closure and wound closure) was recorded. Result: Significant per-operative mean heart rate changes were observed all the events except at wound closure and during anastomosis with D1/D2 and the mean difference of mean of mean arterial pressure at intubations, skin incision, sternotomy, pericardiotomy, during anastomosis of distal end of the graft with RCA, PDA, LCX and D1/D2 were observed statistically significant (p<0.05) . No incidence of different arrhythmia occurred in group B, premature ventricular complex (PVC) was statistically significant (p<0.05) between two groups. Conclusion: HTEA with TIVA appeared to be most comprehensive, allowing for revascularization of any coronary artery, providing good cardiovascular stability during OPCAB. Key Words: CABG; OPCAB; HTEA; TIVA DOI: 10.3329/cardio.v2i2.6633 Cardiovasc. j. 2010; 2(2) : 163-167